2010
DOI: 10.1515/bc.2010.084
|View full text |Cite
|
Sign up to set email alerts
|

Tissue kallikrein promotes prostate cancer cell migration and invasion via a protease-activated receptor-1-dependent signaling pathway

Abstract: We recently demonstrated that tissue kallikrein (TK) promotes keratinocyte migration through activation of protease-activated receptor-1 (PAR(1)) and transactivation of the epi-dermal growth factor receptor (EGFR). In this study, we investigated the potential role of PAR(1) in mediating the effect of TK on cancer cell migration, invasion and proliferation. Our results show that TK promotes DU145 prostate cancer cell migration in a concentration-dependent manner, but has no effect on A549 lung cancer cells. Act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…training days, I hypothesised that the KLK family of serine proteinases might act in a paracrine manner to regulate tissue function by activating PARs. at hypothesis, driving the research of a talented doctoral trainee, Dr. Katerina Oikonomopoulou in the Diamandis laboratory, in collaboration with my own lab, has been amply supported by our own and others ' ndings, that a number of the KLKs can indeed regulate PAR function by either activation or inactivation/disarming [68][69][70]. Of the KLKs we have evaluated, KLKs 5, 6, 8 and 14 each have a di erential ability to regulate KLK function.…”
Section: Kallikrein-related Peptidases (Klks)mentioning
confidence: 76%
“…training days, I hypothesised that the KLK family of serine proteinases might act in a paracrine manner to regulate tissue function by activating PARs. at hypothesis, driving the research of a talented doctoral trainee, Dr. Katerina Oikonomopoulou in the Diamandis laboratory, in collaboration with my own lab, has been amply supported by our own and others ' ndings, that a number of the KLKs can indeed regulate PAR function by either activation or inactivation/disarming [68][69][70]. Of the KLKs we have evaluated, KLKs 5, 6, 8 and 14 each have a di erential ability to regulate KLK function.…”
Section: Kallikrein-related Peptidases (Klks)mentioning
confidence: 76%
“…Ca 2+ mobilization is induced via Gq [31], and is important for the function of several key signaling enzymes, including protein kinase C (PKC), phospholipase A 2 , and calpain [4,39]. In contrast to these divergent Gi and Gq signaling pathways, concomitant Gq and Gi signaling in response to PAR1 activation appears to stimulate ERK1 and ERK2 [40,41]. Direct coupling of PAR1 to G12/13 leads to activation of Rho GEFs, induction of cytoskeletal changes, and PLC activation [30,4245].…”
Section: Exploiting Differences In Par-mediated Signaling For Therapementioning
confidence: 99%
“…Kininogen: KLK1-(brady)kinin system (Marcondes and Antunes, 2005) (Brady)kinin receptor (BKR)2 (Biyashev et al, 2006) PAR1: PAR1-PKC-Src-MMP, keratinocyte migration; migration of prostate cancer cells (Gao et al, 2010a) (Gao et al, 2010b) BKR2, migration of circulating proangiogenic cells (Spinetti et al, 2011) KLK2 uPA (Frenette et al, 1997) KLK4 PAR1, PAR2, (Mize et al, 2008;Ramsay et al, 2008;Gratio et al, 2010) uPA-uPAR (Takayama et al, 2001Beaufort et al, 2006) PAR2 (Stefansson et al, 2008;Gratio et al, 2011;Chung et al, 2012) Brought to you by | University of California -San Francisco Authenticated Download Date | 11/19/14 9:11 AM In terms of the functional consequences of KLK activation of PARs, several studies have demonstrated that these mechanisms regulate important cellular responses in both physiological and pathological settings. For example, KLK1 promotes keratinocyte proliferation and migration in vitro and in an in vivo rat skin wound healing model via a PAR1 dependent, BKR2 independent mechanism requiring downstream activation of PKC and Src resulting in increased matrix metalloproteinase activity (MMP) and regulation of EGFR signalling (Gao et al, 2010a).…”
Section: Klk1mentioning
confidence: 99%
“…For example, KLK1 promotes keratinocyte proliferation and migration in vitro and in an in vivo rat skin wound healing model via a PAR1 dependent, BKR2 independent mechanism requiring downstream activation of PKC and Src resulting in increased matrix metalloproteinase activity (MMP) and regulation of EGFR signalling (Gao et al, 2010a). This group has also recently shown that KLK1, via PAR1, promotes migration and invasion of prostate cancer DU145 but not lung cancer A549 cells (Gao et al, 2010b). Signalling via this PAR and PAR2 induced by both KLK2 and KLK4 enhanced proliferation of prostate cancer DU145 cells (Mize et al, 2008).…”
Section: Klk1mentioning
confidence: 99%